Differential Frequencies of Intermediate Monocyte Subsets Among Individuals Infected With Drug-Sensitive or Drug-Resistant Mycobacterium tuberculosis - Sampath, Pavithra; Natarajan, Alangudi Palaniappan; Moideen, Kadar; Kathamuthu, Gokul Raj; Hissar, Syed; Dhanapal, Madhavan; Jayabal, Lavanya; Ramesh, Paranchi Murugesan; Tripathy, Srikanth Prasad; Ranganathan, Uma Devi; Babu, Subash; Bethunaickan, Ramalingam (Frontiers in Immunology, 2022)
The rampant increase in drug-resistant tuberculosis (TB) remains a major challenge not only for treatment management but also for diagnosis, as well as drug design and development. Drug resistant mycobacteria affect the quality of life owing to the delayed diagnosis and require prolonged treatment with multiple and toxic drugs. The phenotypic modulations defining the immune status of an individual during tuberculosis are well established. The present study aims to explore the phenotypic changes of monocytes & dendritic cells (DC) as well as their subsets across TB disease spectrum, from latency to drug sensitive TB (DS-TB) and drug resistant TB (DR-TB) using traditional immunophenotypic analysis and by uniform manifold approximation and projection (UMAP) analysis. Our results demonstrate changes in frequencies of monocytes (classical, CD14++CD16-, intermediate, CD14++CD16+ and non-classical, CD14+/-CD16++) and dendritic cells (DC) (HLA-DR+CD11c+ myeloid DCs, cross-presenting HLA-DR+CD14-CD141+ myeloid DCs and HLA-DR+CD14-CD16-CD11c-CD123+ plasmacytoid DCs) together with elevated Monocyte to Lymphocyte ratios (MLR) / Neutrophil to Lymphocyte ratios (NLR) and alteration of cytokine levels between DS-TB and DR-TB groups. UMAP analysis revealed significant differential expression of CD14+, CD16+, CD86+ and CD64+ on monocytes and CD123+ on DCs by DR-TB group. Thus, our study reveals differential monocyte and DC subset frequencies among the various TB disease groups towards modulating the immune responses and will be helpful to understand the pathogenicity driven by Mycobacterium tuberculosis.